DEVELOPING VOCABULARY MATERIAL USING LONGTION AUTORUN APPLICATION FOR HEARING IMPAIRED-ELEVENTH GRADE LEARNERS AT SLB NEGERI CERME - Sari, Wulan Purnama (Universitas Muhammadiyah Gresik, 2017)
In the special education, especially hearing impaired learner, the students also learn English, but the learners have the difficulty in learning English vocabulary. There are several reasons for the learners who have the difficulties in learning English vocabulary. One of the reason is because they have physical and mental weakness. Learners of SLB Negeri Cerme also have the difficulties of learning English vocabulary. To help the learners in learning better vocabulary, the researcher will use longtion autorun application to show the picture, text and translation. Longtion autorun application as the base material of learning vocabulary will help learners achieve better vocabularies, which will make the learners more interested and understand the material easily by using some pictures and exercises. The research and development design uses ADDIE instructional design model, to develop vocabulary material using Longtion autorun application for hearing impaired-eleventh grade learners at SLB Negeri Cerme. The research was conducted in SLB Negeri Cerme, involving three hearing impaired learners of eleventh grade. In this research and development, the steps are: need analysis, design, development, implementation, evaluation. The need analysis gave some explanations; First, analysis of interviews with English teacher about the learning need, second, analysis of interviews with learners about their target need and learning need, third, curriculum document analysis. Researcher created a design instruction called material prototype as a framework that was used in developing syllabus and application. Researcher developed a material according to the result of need analysis and design. The activities of the learning are in three phases (pre, whilst, and post) Strategy. From the result of English teacher assessment, the score was 87,5. While the result of learner?s questionnaire about the product, the total score was 88,3. It belongs to the good category based on scoring. This second draft of material was considered as the final draft. The overall conclusion appears that the learners interested when they learnt English using Longtion autorun application because the materials were easy to understand, interesting, and suitable for eleventh grade hearing impaired learners. The researcher gives some recommendation, the next researcher could conduct the similar project to do the same research with different level and focus in order to enrich the variety of the research. For the teacher, this product could be used as a combination when they teach English to introduce the simple English vocabulary to the learners.